BIOMASS CHARACTERIZATION CUPUAÇU BARK (THEOBROMA GRANDIFLORUM) AND AÇAÍ FRUIT STONE (EUTERPE OLERACEA) BIOMASS FOR THE PURPOSE OF REMOVING POTENTIALLY TOXIC METALS FROM CHEMICAL LABORATORY EFFLUENTS - Santos de Sousa , Helayne; Diniz de Oliveira, Jorge (Journal of Interdisciplinary Debates, 2021)
Laboratory effluents are sources of contamination that contribute to serious environmental impacts, especially liquid waste containing potentially toxic heavy metals, when improperly disposed of. A low-cost and good-efficiency alternative for removing metal ions is biosorption. The objective of this work was to characterize the biomass of cupuaçu husk and seed of the fruit of the açaí palm in natura and modified with sodium hydroxide through the parameters: pH in water and KCl, acidic and basic groups and the point of zero charge. It was noticed that the studied characteristics affirm that both in natura and modified biomasses are capable of absorbing potentially toxic metals.